2000
DOI: 10.1038/sj.ijo.0801220
|View full text |Cite
|
Sign up to set email alerts
|

Body fat distribution and cardiovascular risk in normal weight women. Associations with insulin resistance, lipids and plasma leptin

Abstract: OBJECTIVE: To systematically examine the correlations between insulin resistance, plasma leptin concentration, obesity and the distribution of fat assessed by anthropometry and magnetic resonance imaging in Asian women. DESIGN: A cross sectional study of non-diabetic, normal weight women. SUBJECTS: Twenty-one healthy women aged 38.8 y (s.d. 11.7) and BMI 22.6 kgam 2 (s.d. 2.3). MEASUREMENTS: Intraperitoneal, retroperitoneal and subcutaneous abdominal fat volume was assessed by magnetic resonance imaging. Anthr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
47
0
6

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 39 publications
4
47
0
6
Order By: Relevance
“…41 The differential deposition of adipose tissue between the abdominal subcutaneous compartment and the gluteal fat depot is associated with variations in cardiovascular risk factors. 29 Tai et al concluded that there needs to be a shift of focus away from intraabdominal fat to subcutaneous fat when dealing with the features of the metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…41 The differential deposition of adipose tissue between the abdominal subcutaneous compartment and the gluteal fat depot is associated with variations in cardiovascular risk factors. 29 Tai et al concluded that there needs to be a shift of focus away from intraabdominal fat to subcutaneous fat when dealing with the features of the metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%
“…26,27 In turn, an upper body obesity strengthens the risk of the 'Metabolic Syndrome', a constellation of metabolic diseases including dyslipidemia, insulin resistance, hypertension and its clinical consequences like cardiovascular disease and fatty liver. 1,2,28,29 Imaging techniques, that is, magnetic resonance imaging (MRI), computer tomography (CT) and dual-energy X-ray absorptiometry (DEXA), are precise and accurate techniques used to study lean body mass and adipose tissue distribution. However, these techniques are not applicable as field methods because of the risk of radiological burden (CT, DEXA), and the high costs (MRI) limit the measurement to a restricted area.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies on abdominal fat in NW people have found relationships between abdominal fat levels and cardiovascular disease (CVD) or CVD risk factors in NW male subjects [2][3][4] and in some groups of NW female subjects, [5][6][7] but not in others. 8 However, abdominal fat has been suggested to have a greater role in CVD risk in obese female subjects than in obese male subjects. [9][10][11] Hence, some controversy exists regarding sex differences in the role of abdominal fat among NW people.…”
Section: Introductionmentioning
confidence: 99%
“…Adiposity is closely linked to important physiological parameters, such as blood pressure, systemic insulin sensitivity, and fasting triglyceride concentrations (1,2). Visceral fat seems more closely correlated with obesity-associated disorders than overall adiposity (3,4), and is well known to constitute an independent risk factor for myocardial infarction, stroke, type 2 diabetes mellitus, and certain cancers (5,6).…”
mentioning
confidence: 99%